PORNOGRAFI DALAM PERSPEKTIF HUKUM - Dr. Djaenab Djaenab (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Pornography is a legal issue which is rated "low enforcement" in the country, as a result of globalization blaring, he is threatening the future of the nation, especially among the younger generation. Enforcement of pornography in Indonesia is very weak (low enforcement). This happens because of their 'edge areas' of formal legal provisions governing this matter. This relates to the edge of the area prokontra which leads to the perception of pornography itself. Limitation of pornography is very vague and personal. For that need to be made legal provisions to replace the provisions of the law outdated colonial legacy that confirms the so-called pornography. The provisions of the law (ius constituendum) should be an expression of common values ​​in the society of Indonesia, for example, the value of modesty, decency value and so on. However, if the law enforcers could not longer hold back the pace of pornography, especially if they actually take advantage of it that has menggurita and increasingly difficult to eradicate because it involves the circulation of money and manpower are very large, so it's good to do social teraphy considered. No time was right to crack down on pornography in this country, but from this moment. Umbrella law clearer and more unequivocal must be made, so that there are legal restrictions that became the foundation for anyone to act. Do not get tired of people made the pros and cons of pornography without producing anything meaningful. Make the pros and cons of this productive to do for the future of a better nation. Immediately we are concerned about the pornography